Work hazards and workers’ mental health: an investigation based on the fifth European Working Conditions Survey - Russo, Maria; Lucifora, Claudio; Pucciarelli, Francesco; Piccoli, Bruno (La Medicina del Lavoro, 2019)
Background: Workplace hazards are a significant source of health impairment for workers and of financial losses for firms. EU directives on workers’ health and safety standards significantly contributed to reduce reported occupational injuries, yet the incidence and prevalence of work-related mental illness is still very high. Objectives: We investigated the association between work-related hazards and individuals’ perceived mental health. We reviewed the existing evidence on the channels through which task-related factors, adverse agents and psychosocial factors are expected to affect workers’ health, with specific regard to mental health. Methods: We used data from the fifth wave of the European Working Conditions Survey, covering over 40,000 face-to-face interviews with workers in 34 countries, which includes information on socio-demographic characteristics, firms and jobs attributes, employment status, as well as working conditions and health status. We carried out an empirical analysis with multivariate regression models in order to estimate the relationship between workers’ mental health problems and workplace risk factors. Results: 21,020 interviews were used in the multivariate analysis. We found strong correlations between hazards and various indicators of mental health. Among hazardous agents, low temperatures (β=0.0287) and contact with infectious materials (β=0.0394) were positively associated with mental health outcomes. Among task/sequence-related factors, tiring or painful positions (β=0.0713), repetitive hand/arm movements (β=0.0255), working with VDUs (β=0.0301), repetitive tasks